Modelling the causality between FDI and Zimbabwe's economic growth - Mashamhanda, Tendai (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2017)
The study investigates the causal nexus between economic growth and FDI in Zimbabwe for the period spanning 1976 to 2011. The bounds testing approach to cointegration and Granger causality methodology was applied and results suggest a bi-directional causal relationship between FDI and economic growth in the long run. However, the causal effect from economic growth to FDI was weak. Domestic investment, human capital and trade openness were also found to be crucial determinants of economic growth in Zimbabwe. Implementing policies that promote inflow of FDI into Zimbabwe are recommended.
Keywords: Investments, Foreign -- Zimbabwe; Zimbabwe -- Economic conditions -- 1965-1980; Zimbabwe -- Economic conditions -- 1980-